2006
DOI: 10.2174/092986706775476043
|View full text |Cite
|
Sign up to set email alerts
|

Progresses in the Field of Drug Design to Combat Tropical Protozoan Parasitic Diseases

Abstract: The progresses made in the field of drug design to combat tropical protozoan parasitic diseases, such as Chagas' disease, leishmaniasis, and sleeping sickness are discussed. This article is focused on different approaches based on unique aspects of parasites biochemistry and physiology, selecting the more promising molecular targets for drug design. In spite of the enormous amount of work on the above features, the chemotherapy for all of these diseases remains unsolved. It is based on old and fairly not speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 217 publications
(302 reference statements)
0
59
0
4
Order By: Relevance
“…After 2 h of incubation at 37 °C in a 7% CO 2 atmosphere, cultures were washed twice with Hank's solution, and culture medium was replaced to remove extracellular parasites. At this time, 0.5-1 μCi of [5, H] uracil/well (specific activity, 40-50 Ci/mmol) and drug solutions in water were added. Two wells were left for infection control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 h of incubation at 37 °C in a 7% CO 2 atmosphere, cultures were washed twice with Hank's solution, and culture medium was replaced to remove extracellular parasites. At this time, 0.5-1 μCi of [5, H] uracil/well (specific activity, 40-50 Ci/mmol) and drug solutions in water were added. Two wells were left for infection control.…”
Section: Introductionmentioning
confidence: 99%
“…Two wells were left for infection control. Cultures were incubated for 72 h. Incorporation of the [5, H]uracil into trichloroacetic acid (TCA)-precipitable material was measured at day 3. The supernatants from the monolayers were transferred to glass tubes, the cells were dissolved with 1.3 ml of 1% sodium dodecyl sulfate containing 100 μg of cold uracil per ml, and the suspension was transferred to the glass tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, bisphosphonates also have antibacterial (17) and anticancer activities (18) and are able to stimulate ␥␦ T cells (19). Several of these compounds have antiparasitic action (20)(21)(22)(23). It was shown that the enzyme FPPS from these parasites is targeted by bisphosphonates (14).…”
mentioning
confidence: 99%
“…nhibitors of squalene synthase (SQS) have great potential not only as cholesterol-lowering agents (23) but also as antiparasitic drugs (16,37). In trypanosomatids, the enzyme catalyzes the first committed step in isoprenoid biosynthesis that leads to the formation of ergosterol instead of cholesterol such as occurs in mammals (37,38).…”
mentioning
confidence: 99%